(untitled) (Computer systems and information technologies, 2021)
In Europe and the United States, the popularity of independent organizations engaged in testing, inspections and consultations related to the condition or value of the car is growing. They provide breakdown statistics, test results, help estimate the vehicle or the cost of damage. Car manufacturers, insurance companies and car owners use their services. In Ukraine, such services are not yet provided and everyone pays attention to statistics from other countries, which is not very relevant. We decided to develop our own system for analyzing the car reliability. The paper describes the information system of vehicle reliability analysis. The reliability assessment analysis of cars includes the use of methods of statistical modeling and analysis. The purpose of the research is to develop an information system for analyzing the reliability of a car according to information from car services, storing statistics on car maintenance, the formation of annual ratings of car reliability. Information system for car reliability analysis implements the functionality needed to generate a ranking of car reliability for different age categories: 2-3 y. o., 4-5, 6-7, 8-9 and 10-11 y. o. Reliability rankings can be updated once a month, a quarter or a year. The implemented system is based on the car service reservation system. The subject of research is algorithms and methods of implementing the system of vehicle reliability analysis. The essence of this approach is to analyze the information about orders from car service salons in Ukraine. The software product uses the analysis to form car reliability ratings and reports on the average cost of service. For implementation of the system such tools were used: HTML5 markup language; CSS3 style sheet language; SCSS preprocessor scripting language; PHP programming language; Laravel framework; MySQL database management system; OpenServer Panel platform; Visual Studio Code editor; Digital Ocean Web hosting. The results show that this approach can be useful for drivers, official dealers, car manufacturers or insurance companies.